PCSK9 Inhibitors Show Value for Patients and the U.S. Healthcare System - Cheng, Wei-Han (Value Health, 2017)
OBJECTIVES: Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors were approved by the U.S. Food and Drug Administration (FDA) as cholesterol-lowering therapies for patients with familial hypercholesterolemia or atherosclerotic cardiovascular disease. This study estimates the long-term health and economic value of PCSK9 inhibitors for older Americans (aged 51 and older). METHODS: We conducted simulations using the Future Elderly Model (FEM), an established dynamic microsimulation model, to project the lifetime outcomes for the U.S. population aged 51 or older. Health effects estimates and confidence intervals from published meta-analysis studies were used to project changes in life expectancy, quality-adjusted life-years, and lifetime medical spending resulting from use of PCSK9 inhibitors. We considered two treatment scenarios: 1) current FDA eligibility; and 2) an extended eligibility scenario which includes patients with no pre-existing cardiovascular disease (CVD) but at high-risk. We assumed the price of PCSK9 inhibitors was discounted by 35% in the first 12 years and by 57% thereafter, with gradual uptake of the drug in eligible populations. RESULTS: Utilization of PCSK9 inhibitors by individuals covered by current FDA approval would extend life-expectancy at age 51 by an estimated 1.1 years and would yield a lifetime net value of $5,800 per person. If utilization were extended to those at high-risk for CVD, PCSK9 inhibitors would generate a lifetime net benefit of $14,100 per person. CONCLUSION: Expanded access to PCSK9 inhibitors would offer positive long-term net value for patients and the U.S. healthcare system at the current discounted prices.